Should guidance for the use of antihypertensive medication in older people with frailty be different? - van der Wardt, Veronika (Oxford University Press, 2015)
The benefits of antihypertensive treatments have been established in numerous large clinical trials. Although the Hypertension in the Very Elderly Trial (HYVET) confirmed the protective effect of blood pressure medication for healthy, older individuals without dementia over 80 years of age who do not live in a care home [1], the evidence for people who are also frail and/or have comorbidities remains unclear [2]. This is reflected in hypertension guidelines. For example, the guidelines of the European Society of Hypertension and European Society of Cardiology [3] recommend reducing the systolic blood pressure in older people who have a blood pressure of 160 mmHg or above, to between 140 and 150 mmHg with the caveat of those over 80 years of age should be in good physical and mental conditions to do so. The guidelines of the National Institute of Health and Care Excellence (NICE) for Hypertension [4] advise for people under 80 years of age a target blood pressure of 140/90 mmHg and for people over 80 years of age a target blood pressure of 150/90 mmHg. Furthermore, for people over 80 years of age, co-morbidities should be taken into account when deciding on antihypertensive treatment.